Discussion on "An effective method for the explicit solution of sequential problems on the real line" by Sören Christensen. Issue 1 (2nd January 2017) - Buonaguidi, Bruno
ABSTRACT: Let be a geometric Brownian motion, ℙ x be the probability measure under which X starts at x >0, and T be an exponential random variable independent of X . Using the very interesting results presented by Professor Christensen and exploiting the free-boundary problem solution for the optimal exercise of a perpetual American put option, we provide an alternative way to derive the well-known quantity .